PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DAN DAMPAKNYA TERHADAP EFEKTIFITAS ORGANISASI PADA BAGIAN KESEJAHTERAAN RAKYAT SEKRETARIAT DAERAH KABUPATEN KARAWANG - Yeni Maryani (BUANA ILMU, 2018)
ABSTRACT Influence of the quality of Human Resource and motivation to work the Performance of employees and the Impact on the effectiveness of the organization of the people’s welfare regional secretariat District Karawang. the Purpose of this study to obtain empirical evidence and found the clarity of the phenomenon and conclusions about the influence of Quality of Human Resources and Work Motivation Against Employee Performance and Its Impact on Organizational Effectiveness in the Public Welfare Section Karawang District Secretariat. Basedon data analysis, it indicates regression equation Z = 0,35 X1 + 0,62 X2 + 0,889 Y + ԑ1 + ԑ2. The result show that the quality of human resource, motivation to work and the performance of employees perform positive and significant effect on effectiveness of the organization. Determination test indicates that the value of adjusted R square is 0,79 which means that 79%quality of human resource and motivation to work. Meanwhile, 21,1% is affected by other variables which are not investigated in this research Keywords : Quality of Human Resources, Motivation, employee performance and organizational effectiveness